How practitioners conceptualize and operationalize transportation equity in Delaware’s capital expenditure process - Philip Barnes; Andrea L. Pierce; Calaia S. Jackson (Transportation Research Interdisciplinary Perspectives, 2025)
Equitable outcomes are an increasingly important expectation for state Departments of Transportation capital expenditures, yet little is known about the methods and practices used to incorporate the amorphous concept of equity into infrastructure budgetary decisions. This research project employs semi-structured interviews with key personnel in the Delaware Department of Transportation (DelDOT) and local Metropolitan Planning Organizations to illuminate their conceptualization of equity and how it influences capital expenditures for the state’s transportation systems. Utilizing a pre-existing framework for understanding transportation equity, the analysis reveals that practitioners primarily emphasize three dimensions: Fair Share (communities are involved in planning, infrastructure supports non-drivers, and investments are distributed across the state), Inclusivity (infrastructure and mobility systems prioritize accessible options for individuals with special needs), and Social Justice (areas with low-income and minority communities are prioritized for investments, minority-owned businesses receive support for procurement and contracting). DelDOT operationalizes equity through federal requirements and funding, project identification and planning processes, DelDOT’s Equity Analysis Tool, Project Prioritization Criteria used to rank and sort candidate projects, and DelDOT’s Disadvantaged Business Enterprise Program. Practitioner-identified barriers to advancing transportation equity include data quality and availability, and difficulty engaging with underrepresented and hard-to-reach populations. The case study provides valuable insights to other states interested in advancing transportation equity through their capital expenditure process, as well as opportunities to broaden conceptions of transportation equity beyond current practice.